Postexposure prophylaxis for HIV among healthcare workers in Türkiye: a descriptive, multicenter retrospective study - Akca, Veysel; Akbulut, Ilkay; Yilmaz, Gul Ruhsar; Tahmaz, Alper; Oztoprak Cuvalci, Nefise; Esen Yildiz, Ilknur; Togan, Turhan (Tubitak Scientific & Technological Research Council Turkey, 2026)
Background/aim: Postexposure prophylaxis (PEP) for human immunodeficiency virus (HIV) plays a vital role in preventing transmission among healthcare workers following occupational exposure. Despite its clinical importance, epidemiological data regarding PEP implementation in T & uuml;rkiye remain scarce. This study aimed to assess PEP practices, prophylactic treatment regimens, and follow-up outcomes among healthcare workers at risk of occupational HIV exposure. Materials and methods: This retrospective, multicenter study was conducted between January 2020 and December 2024 across 16 healthcare facilities participating in the National HIV/AIDS Working Group. Healthcare workers aged 18 years and older who presented for evaluation following occupational exposure to HIV were included. Data on demographics, exposure characteristics, source patient test results, PEP initiation timing, regimen preferences, adverse effects, and follow-up outcomes were collected from hospital records and analyzed using SPSS v25.0. Results: A total of 369 healthcare workers were assessed. The PEP initiation rate was 49.1%. Needlestick injuries accounted for 79.4% of occupational exposures, and nurses constituted nearly half of presentations (49.6%). In univariable analyses, PEP initiation was less frequent among nurses than among other healthcare staff. In the multivariable model, male sex and age >= 40 years were independently associated with higher odds of PEP initiation, whereas the nursing profession was associated with lower odds. The median time to PEP initiation was 17.9 h (range: 0-120). Adverse effects were uncommon (3.5%), most frequently nausea and vomiting. No HIV seroconversions were identified among individuals with available follow-up results; however, follow-up testing at the predefined time points was incomplete, which limits the ability to exclude rare late seroconversions. Conclusion: Timely initiation of HIV PEP appears feasible and well tolerated in real-world occupational settings. These findings highlight the need for standardized institutional protocols and improved follow-up strategies for healthcare workers in T & uuml;rkiye.
Keywords: Healthcare workers; occupational exposure; needlestick injury; human immunodeficiency virus; postexposure prophylaxis; integrase inhibitor